Determining effective waste human hair hydrolyzing parameters combination and its typical physicochemical characteristics in synthesizing liquid nitrogenous organic fertilizer - Gebremeariam M. K.; Gessese D. A. (Scientific Reports)
Abstract Discarded Human hairs are considered as waste material in most parts of the world and its accumulation causing several environmental problems. However as a potential material resource, human hair has the advantage that it is completely biodegradable, renewable and available in every locality. Thus reutilizing human hair cut discards with a target of extracting a particular major nutrient supply, namely nitrogen, carbon, sulfur and so forth, can create a positive impact on solving soil’s infertility problems and less productivity issues of concerned agrarian communities. This study has tried to develop waste human hair based bio-fertilizer by primarily identify the better performing hydrolyzing mixture rang of formulation (H5), ratio of human hair waste mass to aqueous hydrolyzer mixture usages (1:5), favorable reacting time ( 90 min) and temperature ( 70 oC) values progressively. Then the physicochemical characteristics were analyzed to reveal the resulted final product’s viscosity (~ 76.0 cp.), density (~ 1.17 gm/l), pH (~ pH 9), organic nutrients availability concerning primary Macronutrients (~ 18:0.03:1 N-P-K ratio ), Secondary Macronutrients (~ 0.13:0:7 Ca-Mg-S ratio) and other trace micronutrient constituents; which are considered as requirements for the soil nutrient enrichments and plant growths.